165k views
0 votes
Solve for x -5(-x+1)-3x-1=-12

User Shayna
by
4.9k points

2 Answers

1 vote
i got -3 i don’t know if it’s right by looking at the other answers
User Abdul Rehman Sayed
by
6.1k points
3 votes

Answer:

x = -2

General Formulas and Concepts:

Order of Operations: BPEMDAS

Explanation:

Step 1: Define equation

x - 5(-x + 1) - 3x - 1 = -12

Step 2: Solve for x

  1. Distribute -5: x + 5x - 5 - 3x - 1 = -12
  2. Combine like terms: 3x - 6 = -12
  3. Add 6 to both sides: 3x = -6
  4. Divide 3 on both sides: x = -2

Step 3: Check

Plug in x to verify it's a solution.

  1. Substitute: -2 - 5(-(-2) + 1) - 3(-2) - 1 = -12
  2. Multiply: -2 - 5(2 + 1) + 6 - 1 = -12
  3. Add: -2 - 5(3) + 6 - 1 = -12
  4. Multiply: -2 - 15 + 6 - 1 = -12
  5. Subtract: -17 + 6 - 1 = -12
  6. Add: -11 - 1 = -12
  7. Subtract: -12 = -12
User Adaleni
by
5.7k points